Pembiayaan Murabahah Bi al-Wakalah pada Koperasi Jasa Keuangan Syari’ah Muamalah Berkah Sejahtera Surabaya - Mujibur Rido (Maliyah : Jurnal Hukum Bisnis Islam, 2019)
This article discusses Murabahah bil Wakalah Risk Management at KJKS Muamalah Berkah Surabaya. This study uses a qualitative descriptive design by describing the operational and risk management of murabahah bil wakalah financing at KJKS MBS through observation and interviews. The results of this study are 1. Active murabahah bil wakalah financing in the Syari'ah Muamalah Berkah Sejahtera Financial Services Cooperative is that the customer is interviewed first to determine the purpose of the loan. The customer must meet the requirements that the MBS KJKS has selected; after that, the MBS KJKS explained the procedure for applying for financing. The MBS KJKS gave the right to purchase goods to the customer accompanied by a murabahah contract and provided an installment savings book. 2. In the risk management of murabahah bil wakalah, there are three: First, for liquidity risk management, KJKS MBS invests funds in Islamic banks in the event of excess liquidity and borrows funds from Islamic banks when there is an excess of liquidity. Lack of liquid. Second, for risk management of credit congestion, KJKS MBS uses monthly billing to customers' homes and discounts customers who pay off their outstanding debts. Third, for capital risk management KJKS MBS uses reserve funds to cover losses.